RESEARCH OF LEGAL REGULATION OF PERSONNEL SAFETY OF THE PHARMACEUTICAL ORGANIZATIONS IN RUSSIA - A KUZNETSOV, DMITRY; U KLISСHENKO MARINA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The study consists in the analysis of the main regulatory acts governing personnel safety in pharmaceutical organizations. In the process of managing a pharmaceutical organization, the leader must rely on the requirements of current legislation in the field of personnel safety. Safety is the main strategic activity of any pharmaceutical organization. The legal framework governing personnel security is constantly expanding. Actually study the fundamental standards of personnel safety. Methods: The methods of analysis were a systematic approach, logical grouping, content analysis of the main documents regulating personnel security in the pharmaceutical industry. Results: The fundamental regulatory acts were identified that play a major role in ensuring and regulating the personnel safety of pharmaceutical organizations. Personnel security is a key element of the economic security of a pharmaceutical organization. The management of pharmaceutical personnel in the personnel safety system consists in finding ways to minimize risks and threats from and in relation to employees. The basic regulatory acts in the system of personnel security are identified, which allow to level threats and optimize the sustainable development of the pharmaceutical organization. Conclusion: In Russia, the legal basis for the personnel security of pharmaceutical organizations is: the Constitution; international treaties; federal constitutional laws; federal laws and regulations; Government Decisions; laws and other regulatory legal acts of entities. The term “security” is introduced by the law “On Security”. The main security threats are identified in the Economic Security Strategy for the period until 2030.